2000
DOI: 10.1021/ja992543i
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chiral Mixed Phosphorus/Sulfur Ligands to Palladium-Catalyzed Allylic Substitutions

Abstract: A modular approach to the synthesis of a class of mixed phosphorus/sulfur ligands was designed to identify important ligand structural features for enantioselective palladium-catalyzed allylic subsitutions of acyclic and cyclic ayllic esters. After a systematic variation of the ligand substituents at sulfur, phosphorus, and the ligand backbone, ligand 11k was found to be optimal in the palladium-catalyzed allylic substitution of 1,3-diphenylpropenyl acetate with dimethyl malonate or benzylamine in high yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
144
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(152 citation statements)
references
References 57 publications
6
144
0
2
Order By: Relevance
“…The proposal that nucleophilic attack occurs in an S N 2Ј fashion with inversion is consistent with the well documented mechanism of palladium -allyl chemistry (73)(74)(75)(76) and the proposed mechanism of rhodium-catalyzed reactions of allylic carbonates put forward by Evans (12). The proposal that the alkoxide moiety directs the nucleophilic attack by shifting the position of the metal on the allyl fragment has precedent in the chemistry of palladium where neighboring groups have been found to exert this type of directing influence (77,78).…”
Section: Discussionsupporting
confidence: 79%
“…The proposal that nucleophilic attack occurs in an S N 2Ј fashion with inversion is consistent with the well documented mechanism of palladium -allyl chemistry (73)(74)(75)(76) and the proposed mechanism of rhodium-catalyzed reactions of allylic carbonates put forward by Evans (12). The proposal that the alkoxide moiety directs the nucleophilic attack by shifting the position of the metal on the allyl fragment has precedent in the chemistry of palladium where neighboring groups have been found to exert this type of directing influence (77,78).…”
Section: Discussionsupporting
confidence: 79%
“…Planar chiral ferrocene derivatives are extensively used as ligands in versatile reactions of asymmetric synthesis [1][2][3][4][5][6][7][8][9][10]. An important place among the ligands of the ferroce series belongs to heterocyclic derivatives capable of forming complexes with metals and also with charged and neutral molecules [1,11].…”
mentioning
confidence: 99%
“…The close proximity of the chiral sulfur atom to the coordination sphere of the transition metal anticipates a good enantioselective discrimination in the catalytic process, provided that the low inversion barrier of the sulfur metal bond can be surmounted. 5,7 We have recently reported the preparation of C 2 -symmetric bis-thioglycosides as new homodonor S/S ligands in Pd(0)-catalyzed allylic alkylation of 1,3-diphenylpropenylacetate with dimethyl malonate.8 A subsequent study of the corresponding Pd(II) complexes has indicated that the good enantioselectivity achieved was a consequence of an efficient stereocontrol of the sulfur atom exerted by the exo-anomeric effect. 9 In the case of phosphinite thioglycosides I metal complexes, where the exo-anomeric effect is not operative, good stereocontrol of the sulfur atom is also predicted taking into account the strong steric and stereoelectronic interactions of the substituent at sulfur and the endocyclic oxygen of the pyranose ring.…”
mentioning
confidence: 99%
“…The close proximity of the chiral sulfur atom to the coordination sphere of the transition metal anticipates a good enantioselective discrimination in the catalytic process, provided that the low inversion barrier of the sulfur metal bond can be surmounted. 5,7 We have recently reported the preparation of C 2 -symmetric bis-thioglycosides as new homodonor S/S ligands in Pd(0)-catalyzed allylic alkylation of 1,3-diphenylpropenylacetate with dimethyl malonate.…”
mentioning
confidence: 99%
See 1 more Smart Citation